Enhanced heat transfer and flow dynamics of Powell-Eyring nanofluid: unsteady stretched surface and with Stefan blowing/suction - Kalyan Kumar Challa; M. Eswara Rao; Muhammad Jawad; Taoufik Saidani; Suhad Ali Osman Abdallah; Thenmozhi D (Case Studies in Thermal Engineering)
The current study examines the flow characteristics of Powell- Eyring nanofluid passing over an unsteady stretched surface subject to Stefan blowing/suction. The motivation stanches from the prerequisite to comprehend progressive heat and mass transfer characteristics and their insinuations for science, engineering and industrial system. New aspects related to Brownian motion and thermophoresis with heat transfer are examined. Through similarity variables, the governing partial differential equations of Powell- Eyring nanofluid model are transformed into ordinary differential equations. Numerical solutions are obtained using the fourth-order RK method combined with a shooting approach. The impression of involving parameters on emerging profiles are discussed via graph, table and literature. The results reveal that velocity increases with variations in Powell-Eyring fluid parameter. Additionally, fluid temperature increases with variations in fluid parameter, magnetic field, and unsteadiness parameter. Remarkably, the fluid's temperature rises while its nanoparticles concentration decreases with higher Brownian motion parameter values. It is observed the velocity curve is decreased for increasing value of magnetics number.